Ecological Urbanism: metabolic rift and phantasmagoria - Figueirôa-Ferreira, Victor Garcia; Borchers, Tatiane; Fernandes, Ricardo Augusto Souza (Revista Nacional de Gerenciamento de Cidades, 2022)
This article seeks to contribute to the argument that Ecological Urbanism is a movement or a valid concept to promote resilience, sustainability and a socio-environmental diversity that values localities, presenting a resistance to hegemonic processes and patterns of a globalized urbanism. In this sense, a literature review and analysis was carried out regarding ecological urbanism itself, as well as the metabolic rift, in order to contribute to its ecological aspect and the phantasmagoria to approach its urban side. Defending the use of historical materialism in the analysis of urban space and the city, as well as the social, political, cultural and economic relations that permeate urban ecologies.